Effects of Visual Training on the Reaction Time among Badminton Athletes (ACPES Journal of Physical Education, Sport, and Health (AJPESH), 2022)
This study aims to identify the effects of visual training on the reaction time among badminton athletes using two reaction time tests, namely, the Whole-Body Reaction Time (WBRT) and the Finger Reaction Time (FRT). This quasi-experimental study involves 30 badminton athletes (Male = 30, Female = 30). The study involved two groups [treatment group = 30, control group = 30]. The descriptive analysis undertaken shows that the level of reaction time of treatment group for the pre-WBRT test is (M = 0.32, SD = 0.047) and pre-FRT test is (M = 0.48, SD = 0.068). For group control, the pre-WBRT test is (M = 0.33, SD = 0.030) and the pre-FRT test is (M = 0.49, SD = 0.065). On the other hand, the reaction time of treatment group for the post-WBRT test is (M = 0.28, SD = 0.037) and post-FRT test is (M = 0.41, SD = 0.054). Meanwhile, for control group, the post-WBRT test is (M = 0.32, SD = 0.037) and post-FRT test is (M = 0.45, SD = 0.061). Furthermore, for treatment group, there is a significant difference between the pre- and post-WBRT test [t (29) = 8.813, p = .000] and the FRT test [t (29) = 10.329, p = .000]. As for control group, there is also a significant difference between the pre- and post-WBRT test [t (29) = 3.786, p = .001] and the FRT test [t (29) = 4.935, p = .000]. Nevertheless, there is no significant difference between both the two pre-WBRT test group [t (58) = 1.667, p = .101] and the FRT test group [t (58) = 0.546, p = .587]. However, there is a significant difference for both the post-WBRT test group [t (58) = 4.676, p = .000] and the FRT test group [t (58) = 3.056, p = .003]. Overall, this study can help coaches in designing effective training programs which can help to enhance the reaction time level of badminton athletes.